Effects of a ritonavir‐containing regimen on the pharmacokinetics of sirolimus or everolimus in healthy adult subjects - Zha, Jiuhong; Jiang, Qi; Yao, Betty B.; Cohen, Daniel E.; Carter, David C.; Menon, Rajeev M. (Pharmacology research & perspectives, 2022)
The immunosuppressive agents sirolimus and everolimus are sensitive CYP3A4 substrates with narrow therapeutic index. Ritonavir is a strong CYP3A inhibitor. A phase 1 study was conducted to evaluate the pharmacokinetics, safety, and tolerability of the co‐administration of sirolimus or everolimus with the ritonavir‐containing 3D regimen of the direct‐acting antiviral agents ombitasvir, ritonavir‐boosted paritaprevir, and dasabuvir in healthy subjects. This study had two independent arms, each with a two‐period, single‐sequence, crossover study design. A single dose of sirolimus 2 mg (N = 12) or everolimus 0.75 mg (N = 12) was administered in Period 1. In Period 2, multiple doses of the 3D regimen (ombitasvir/paritaprevir/ritonavir 25/150/100 mg once daily and dasabuvir 250 mg twice daily) were administered for 34 or 28 days, with a single dose of sirolimus 0.5 mg or everolimus 0.75 mg co‐administered on Day 15. Following co‐administration with the 3D regimen, the sirolimus dose‐normalized maximum observed blood concentration (Cmax) and area under the blood concentration–time curve from time zero to infinity (AUCinf) increased to 6.4‐fold and 38‐fold, respectively. Following co‐administration with the 3D regimen, the everolimus Cmax and AUCinf increased to 4.7‐fold and 27‐fold, respectively. Sirolimus and everolimus half‐lives increased from 96 to 249 h, and 42 to 118 h, respectively. There were no major safety or tolerability issues in this study. The ritonavir‐containing 3D regimen resulted in a significant increase in sirolimus or everolimus exposure, consistent with the known strong inhibitory effect of ritonavir on CYP3A requiring dose and/or frequency modification when co‐administered with each other. When co‐administered with the ritonavir‐containing 3D regimen, sirolimus and everolimus exposures (AUC) increased to 38‐fold and 27‐fold, respectively. The study results can be used to guide dose recommendation for sirolimus or everolimus when co‐administered with ritonavir‐containing regimens.